Judicial bypass attorneys' experiences with abortion stigma in Texas courts. (January 2021) - Coleman-Minahan, Kate; Stevenson, Amanda Jean; Obront, Emily; Hays, Susan
Abstract: Texas requires pregnant young people under 18 (i.e., minors) seeking abortion without parental consent to go to court with an attorney to petition a judge for permission to obtain abortion. There is a lack of empirical data on the process through which abortion laws stigmatize abortion and on the actors involved. We use data from in-depth qualitative interviews with 19 attorneys who participated in a collective 800 judicial bypass cases to explore what's at stake for multiple actors within a shared social space and how interactions between those actors reproduce stigma. We extend stigma theory to explain how structural abortion restrictions produce stigma at the individual level. We find that to protect their interests in "keeping pregnant minors in, " the Texas court system constrains attorneys' ability to represent minors through politicization and stigmatization; attorneys face logistical and emotional challenges, including navigating hostile or ill-informed courts, witnessing court actors humiliate their clients without means of recourse, and experiencing stigma themselves. Although what's most at stake for their clients becomes most at stake for attorneys— helping young people obtain a judicial bypass so they can access abortion and protecting them from humiliation and trauma— they must reconcile their own violation of norms stigmatizing abortion with their consciences' motivation to represent bypass clients and protect their professional identity and career advancement from being "tainted" by taking judicial bypass cases. In order to protect what is at stake for their clients in the context of the highly stigmatized Texas courts, attorneys rationally make trade-offs that protect some stakes while undermining others. Moreover, attorneys' management of experienced stigma and their violation of norms stigmatizing abortion leads some to reproduce abortion stigma in their interactions with minors. Highlights: Multi-level abortion stigma is reinforced by the judicial bypass process. Texas courts constrain attorneys' ability to represent minors through politicization. Attorneys experience associative stigma by representing minors seeking abortion. Attorneys stratify legitimate bypasses to protect population-level abortion access.